2017
DOI: 10.1681/asn.2016090980
|View full text |Cite
|
Sign up to set email alerts
|

Apixaban Pharmacokinetics at Steady State in Hemodialysis Patients

Abstract: It is unclear whether warfarin is protective or harmful in patients with ESRD and atrial fibrillation. This state of equipoise raises the question of whether alternative anticoagulants may have a therapeutic role. We aimed to determine apixaban pharmacokinetics at steady state in patients on hemodialysis. Seven patients received apixaban 2.5 mg twice daily for 8 days. Blood samples were collected before and after apixaban administration on days 1 and 8 (nondialysis days). Significant accumulation of the drug w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
151
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(165 citation statements)
references
References 32 publications
5
151
0
9
Order By: Relevance
“…Drug levels comparing day 5 versus day 8 suggested that a steady state had been reached. Despite that it still would be of interest to examine levels with a longer duration of exposure (52).…”
Section: Pharmacology In Kidney Diseasementioning
confidence: 99%
“…Drug levels comparing day 5 versus day 8 suggested that a steady state had been reached. Despite that it still would be of interest to examine levels with a longer duration of exposure (52).…”
Section: Pharmacology In Kidney Diseasementioning
confidence: 99%
“…New steady‐state pharmacokinetic evidence evaluating NVAF patients undergoing thrice‐weekly 4‐hour hemodialysis sessions has emerged, indicating apixaban 5 mg twice/day may lead to supratherapeutic apixaban levels (observed in two of five patients) . Apixaban 2.5 mg twice/day in the same five patients (average age 62 years, body mass index 32.9 kg/m 2 ) led to mean apixaban peak, trough, and area under the concentration‐time curve (AUC) levels comparable to the reference range determined in the ARISTOTLE trial . However, the authors also reported the 24‐hour AUC fell below the 10th percentile in three of five patients with the 2.5 mg twice/day dosage in the hemodialysis population .…”
mentioning
confidence: 80%
“…Apixaban 2.5 mg twice/day in the same five patients (average age 62 years, body mass index 32.9 kg/m 2 ) led to mean apixaban peak, trough, and area under the concentration‐time curve (AUC) levels comparable to the reference range determined in the ARISTOTLE trial . However, the authors also reported the 24‐hour AUC fell below the 10th percentile in three of five patients with the 2.5 mg twice/day dosage in the hemodialysis population . The authors concluded that while apixaban may be a reasonable alternative in hemodialysis, the 5 mg twice/day dosage should be avoided …”
mentioning
confidence: 85%
“…Among DOACs, apixaban is the least dependent on renal clearance of the direct factor Xa inhibitors and might be the one with the smallest bleeding risk 4. As a matter of fact, there is some pharmacokinetic evidence to support the use of an adjusted dose of apixaban in patients on HD 5. However, individuals with severely impaired kidney function and concomitant HIT are underrepresented in the medical literature.…”
Section: Discussionmentioning
confidence: 99%